2003
DOI: 10.1080/02781070310001015107
|View full text |Cite
|
Sign up to set email alerts
|

On the apollonian metric of domains in

Abstract: We study the apollonian metric considered for sets in R n by Beardon in 1995. This metric was first introduced for plane Jordan domains by Barbilian in 1934. For a special class of plane domains Beardon showed that conformal apollonian isometries are Mo¨bius transformations. We give here a proof of Beardon's result without conformality assumption. We show that the apollonian metric of a domain D is either conformal at every point of D, at only one point of D or at no point of D. We also present a suprising rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In the view of Theorem 2, it might be of interest to note that Zair Ibragimov has shown that the Barbilian metric is Riemannian in zero, one or all points of the domain (he uses the term "conformal" for Riemannian). See [24], [25] for this fact and related implications.…”
Section: What Classes Of Metrics Does Barbilian Metrization Procedurementioning
confidence: 99%
See 2 more Smart Citations
“…In the view of Theorem 2, it might be of interest to note that Zair Ibragimov has shown that the Barbilian metric is Riemannian in zero, one or all points of the domain (he uses the term "conformal" for Riemannian). See [24], [25] for this fact and related implications.…”
Section: What Classes Of Metrics Does Barbilian Metrization Procedurementioning
confidence: 99%
“…Later contributions on the topic of Barbilian spaces include P. J. Kelly's work [26] and major developments are due to D. Barbilian himself [3], [4], [5], [6]. Recently, many citations of the work [2], originally published in Časopis Mathematiky a Fysiky, have appeared, for example, in [7], [11], [13], [16], [18], [19], [20], [21], [22], [23], [24], [25]. The history of this subject is presented in [14], [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This note is motivated by the recent increased attention to Barbilian's work (see the references at the end to Beardon, 1998;Boskoff, 1993Boskoff, , 1994Boskoff, , 1995Boskoff, , 1996aBoskoff, , 1996bBoskoff, , 1998Boskoff, , 2002Boskoff and Horja, 1994;Gehring and Hag, 2000;Hästö, 2003aHästö, , 2003bHästö, , 2004aHästö, , 2004bHästö, , 2006Hästö and Ibragimov, 2007;Hästö and Lindén, 2004;Ibragimov, 2002Ibragimov, , 2003aIbragimov, , 2003band Souza, 1999). Barbilian had a profound impact on 20th century Romanian arts and culture through his contributions in literature and mathematics.…”
mentioning
confidence: 98%
“…In [13,Theorem 2] he showed that for the Apollonian metric either none, one or all points are points of conformality. The middle case provides an interesting link to convex sets of constant width, see [13,Theorem 3]. We say that a domain G R n is quasi-isotropic if (G, α G ) is, similarly for isotropic.…”
Section: The Apollonian Spheres and Quasi-isotropymentioning
confidence: 99%